2019
DOI: 10.1016/j.heliyon.2019.e02905
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum DDX31 is DNA helicase localized in nucleolus

Abstract: Malaria is a major infectious disease and is responsible for millions of infections every year. As drug resistance strains of Plasmodium species are emerging, there is an urgent need to understand the parasite biology and identify new drug targets. Helicases are very important enzymes that participate in various nucleic acid metabolic processes. Previously we have reported several putative DEAD box helicases in the genome of Plasmodium falciparum 3D7 strain. In this study, we present biochemical characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…The transcription and translation for a particular gene could be different in different stages of the parasite [ 32 ]. Previously, we have reported that gene expression of PfDDX31, ATP dependent DNA helicase, is more in schizont stage but the transcript level is more in ring stage [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transcription and translation for a particular gene could be different in different stages of the parasite [ 32 ]. Previously, we have reported that gene expression of PfDDX31, ATP dependent DNA helicase, is more in schizont stage but the transcript level is more in ring stage [ 35 ].…”
Section: Discussionmentioning
confidence: 99%